The responsibility to protect ending mass atrocity crimes once and for all - Evans, Gareth J., 1944-; ProQuest (Firm). (Washington, D.C. : Brookings Institution Press, 2008)
"Explains Responsibility to Protect (R2P), a new international norm to protect the peoples of the world. With real-world examples, current events analysis, and assessments from personal experience, shows how R2P is better equipped to end mass atrocity crimes than is "the right to intervene" or other "humanitarian intervention" doctrines"--Provided by publisher.
The problem : the recurring nightmare of mass atrocities -- The solution : from "the right to intervene" to "the responsibility to protect" -- The scope and limits of the responsibility to protect -- Before the crisis : the responsibility to prevent -- During the crisis : the responsibility to react -- Responding to crises : when is it right to fight? -- After the crisis : the responsibility to rebuild -- Institutional preparedness : the actors.
Off-Campus Access: Athens ID and Password Required
On-Campus Access: No User ID or Password Required
Access type: Perpetual access for unlimited users
Includes bibliographical references and index.
ARC, PPDM
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Atrocities -- Prevention; Genocide -- Prevention; Responsibility to protect (International law).; Electronic books